127 Serial Monitoring of Left Ventricular Ejection Fraction in Patients with Haematological Malignancies Receiving Anthracycline-Based Chemotherapy. (3rd June 2016) - Demetriades, Polyvios; Ho, Emily
Abstract : Introduction: Anthracyclines are one of the most widely used chemotherapeutic agents. However, their use has been limited due to significant risk of cardiotoxicity. This has been reported in 6.2% of adult patients with haeamatological malignancies. Early-onset cardiotoxicity is by far the commonest, occurs within the first year following treatment and manifests as a form of dilated cardiomyopathy. Early detection with imaging, even in asymptomatic patients, and appropriate treatment with anti-failure medication leads to recovery of left ventricular function (LVEF) in up to 82% of patients. This highlights the need for a consensus strategy to guide monitoring frequency and duration in the long-term management of these patients. We conducted a quality improvement project to review the current practice in the Haematology department of our Trust. Methods: We identified patients with haematological malignancies that were commenced on anthracycline-based chemotherapy regimens between March 2014 and August 2015. We collected data regarding pre and post-chemotherapy imaging with echocardiograms and compared our findings against the recommendations of the "ESMO Clinical Practice Guidelines". These suggest that all patients should have serial monitoring of their LVEF at baseline and at 3-monthly intervals for the first year post-treatment. In addition, we performed a qualitative analysis to review the management of the patients with abnormal echocardiograms both pre and post-chemotherapy. Results: We identified a total of 83 patients, of which 74.7% were treated with doxorubicin-based chemotherapy. The majority of patients (96.4%) had a baseline echocardiogram to assess LVEF prior to chemotherapy. However, only 29 patients (34.9%) had imaging post-chemotherapy. Unfortunately, in the majority (n = 18) this was requested due to symptoms rather than as part of serial monitoring. Of our cohort, six patients had a degree of left ventricular systolic dysfunction (mild to moderate) prior to chemotherapy but proceeded without any cardiology input. Of these, only 50% had an echocardiogram post-chemotherapy. In total, three patients developed impairment of left ventricular function post-chemotherapy due to anthracycline cardiotoxicity. Discussion and conclusion: We identified a significant lack of awareness on the monitoring strategies of patients receiving anthracycline-based chemotherapy possibly reflecting the lack of local guidelines. As a result, we introduced an algorithm that will guide the management of these patients (Fig 1 ). In conclusion, our project has highlighted an area of clinical practice that requires effective communication and collaboration between different specialties. We strongly encourage clinicians to review their local practices and implement strategies to allow early identification and management of anthracycline-induced cardiotoxicity to prevent further morbidity and mortality.